Study of Satisfaction of Information System Users in Study Program (SIMPRODI) in Gorontalo State University - Rizan Machmud (International Journal of Applied Business and International Management, 2018)
The rapid development of Information Technology (IT) today provides many conveniences in various forms of business, including the service business. System User Satisfaction (User satisfaction) is the response and feedback that the user raises after using the information system. This study aims to obtain empirical evidence regarding the use of SIMPRODI application products and how SIMPRODI can provide good services for students. The survey research method was carried out and the data collected was 252 data. The data was then analyzed by PLS-SEM. The results showed that the quality of the system did not have a significant effect on the SIMPRODI intention to use, but the quality of information and quality of service was significant on the intention to use, then when the intention to use was higher the user satisfaction was better and vice versa when the SIMPRODI user satisfaction was high then intention to use is also getting higher.